BANGUNAN KARAKTER QUR’ANI (Analisis Konsep Pendidikan Karakter dalam Perspektif Wahyu) - Shidiq, Ngarifin; Rohani, Rohani (Manarul Qur'an: Jurnal Ilmiah Studi Islam, 2025)
This research aims to examine and elaborate on the concept of character education in the perspective of revelation, especially theQur'an, as a basic paradigm in the formation of human personality. This study is a qualitative research with a library researchapproach, using the Miles and Huberman analysis method which includes data reduction, data presentation, and conclusion drawn.Data was obtained from literature sources such as books, scientific articles, journals, and verses of the Qur'an related to charactervalues. The results of the study show that the Qur'an is not only a source of law and worship, but also a comprehensive moralguideline in forming noble morals (al-akhlaq al-karimah). The concept of character in the Qur'an encompasses two dimensions:man's relationship with Allah (hablum min Allah) and his relationship with fellow creatures (hablum min al-nas), which is reflectedin values such as honesty, trust, tawakal, gratitude, patience, and compassion. These values are internalized through an educationalprocess that involves family, school, and community as a character education ecosystem. This study emphasizes the importance of making the Qur'an a paradigm in building the nation's character, as a form of response to moral crises and moral degradation thatoccur in the midst of scientific and technological developments. The Qur'anic paradigm in character education is oriented towardsthe formation of a whole human being (insān kāmil) who is able to actualize spiritual, moral, and social values in daily life.